Effect of high-intensity interval training on anaerobic capacity in ITF taekwondo practitioners - Batra, A.; Zaton, M. (Journal of Combat Sports and Martial Arts, 2017)
Purpose. The purpose of the study was to investigate the effects of high-intensity interval training on anaerobic capacity in taekwondo athletes. Materials and methods. The study recruited 20 male International Taekwondo Federation-style practitioners that were randomly divided into an experimental (n=10) and a control (n=10) group. The control group (C) executed a regular training protocol (five 90-min sessions per week) involving traditional TKD methods and techniques for 8 weeks. During the same timeframe, the experimental group (E) followed the same TKD training regime as group C except two of the five sessions were substituted with interval training-based TKD exercise involving 30 s of maximal kicking drills (round middle kick) separated by 90 s of rest. Anaerobic capacity and power were measured pre- and post-training by the 30-s Wingate cycle ergometer test. Results. Post-training values of peak power, total work output, and time of sustained peak power increased only in group E. Group E was also characterized by a significant post-training increase in minute ventilation (VE) and blood lactate (LA-). No significant changes were observed in group C. Connlusions. The inclusion of interval training-based exercise significantly enhanced anaerobic power and capacity in taekwondo practitioners.